2011
DOI: 10.1007/s00330-011-2214-3
|View full text |Cite
|
Sign up to set email alerts
|

The value of flat-detector computed tomography during catheterisation of congenital heart disease

Abstract: FD-CT provides useful diagnostic information in most of the patients investigated for congenital heart disease. The added radiation exposure and contrast medium volume are reasonable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…The 3D model can be produced from different imaging modalities, such as CT, magnetic resonance, or ultrasound images. In cardiology, its use is limited to radiofrequency‐based atrial fibrillation ablation procedures and to complex rythmological and hemodynamic interventions in congenital heart diseases patients . So far, all of these evaluations are limited to feasibility studies or case reports providing a subjective evaluation of the contributions of this technology.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D model can be produced from different imaging modalities, such as CT, magnetic resonance, or ultrasound images. In cardiology, its use is limited to radiofrequency‐based atrial fibrillation ablation procedures and to complex rythmological and hemodynamic interventions in congenital heart diseases patients . So far, all of these evaluations are limited to feasibility studies or case reports providing a subjective evaluation of the contributions of this technology.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the scarce information in the literature 5,19,20 , the use of 3D-RA in this context reduces the number of necessary acquisitions and brings the possibility of increasing accuracy in the assessment of patients with defects with a complex anatomy; however, it is not yet well established whether 3D-RA adds information on these defects.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Glockler et al 19 evaluated and reported their experience in 62 patients with a median weight of 14.4 Kg undergoing rotational angiography for the assessment of pulmonary arteries, aorta, and cavopulmonary connections. In this study, the images were considered superior to those of conventional angiography in 90.3% of cases and very useful for guiding interventional procedures using overlaying three-dimensional images.…”
Section: Discussionmentioning
confidence: 99%
“…This was done in compliance with the International Commission on Radiological Protection 103 guidelines [17]. Radiation dose and the irradiated area were measured in the collimator housing, independent from the patient distance [18]. Out of these system reported doses the radiation dose in μGym²/kg was calculated for the 483 cases and compared between the diagnostic program and the low dose program.…”
Section: Methodsmentioning
confidence: 99%